IMPLEMENTASI MOODLE PENGELOLAAN PEMBELAJARAN KELAS X SMA NEGERI 12 SIJUNJUNG - Yulian Fanda (JURTEII: Jurnal Teknologi Informasi, 2021)
The process of learning in SMA Negeri 12 Sijunjung still use the conventional way through face-to-face between teacher and students. Learning methods such as these have limitations that may hamper the delivery of science that developed quickly due to the limitations of time and place. From this condition then the e-Learning System is expected to become an alternative solution to overcoming existing limitations on SMA Negeri 12 Sijunjung especially in Class X. The goal of the research is to make it easy for teachers and students in teaching and learning activities, facilitate the access of all forms in the process of teaching and learning activities and make it easier to accept the results or information from the teaching and learning activities. As for the benefits that can be gained from the analysis and design of web-based E-learning it is can make it easier for students to obtain material and lessons, allowing teachers to distribute subject matter, open communication between teachers and students or between students outside of lessons through discussion forums. Development of e-learning uses a Content Management System (CMS) Moodle, while analysis using Flow Information System, for designing system using Hyrarcy Plus Input-Process-Output (HIPO), Data Flow diagrams (DFD), and Entity Relationship Diagram (ERD).